Synthesis of new flame retardant materials and smoke suppressants based on modified magnesium hydroxide for ABS copolymer and polystyrene - Emad Sobhy Mohamed Goda; Magdy Sabaa Wadid Farag Sabaa; Mohamed Aly Hassan (Cairo : Emad Sobhy Mohamed Goda, 2016)
The presented thesis is oriented to a new developed method for the synthesis and modification of magnesium hydroxide nanoparticles (MH-NPs) using the ball milling technique in the presence of organic phosphate compounds which were maleate monophosphate (MP), maleate diphosphate (DP), polymaleate diphosphate (PDP) and polymaleate monophosphate (PMP). The size of MH-NPs was controlled using the developed method with diameter range from 46-125 nm. The inclusion of these nanoparticles in acrylonitrile-butadiene styrene (ABS) and polystyrene (PS) were done producing well dispersed nanocomposites. The MH-NPs and the new polymer nanocomposites were characterized using fourier transform infrared (FTIR), transmittance electron microscope (TEM), thermogravimetric analysis (TGA) and scanning electron microscope (SEM). The flammability and smoke measurements for the new nanocomposites were studied using UL94 flame chamber, cone calorimeter and smoke density chamber. The rate of burning of the ABS nanocomposites was reduced to 9.8 mm.min-1 compared to 42.5 mm.min-1 for the virgin polymer and the burning rate of PS nanocomposites was reduced by 75% compared to the pure PS. The peak heat release rate (PHRR) of the new ABS and PS nanocomposites were reduced by 71,68% compared to the pure polymers, respectively. The smoke properties (maximum specific optical density Dm) for the developed ABS and PS nanocomposites were significantly reduced achieving 62% and 46% reduction compared to pure ABS and PS
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Organic Chemistry
Issued also as CD
Keywords: Flammability; Magnesium hydroxide nanoparticles; Nanocomposites